ASSOCIATION OF CHRONIC LOW BACK PAIN AND DEPRESSION AT A TERTIARY CARE SETTING OF PAKISTAN - Rabia Siddiqui; Saif Ullah Shaikh; Najmus Sahar; Muhammad Faisal Fahim (Journal of Postgraduate Medical Institute, 2023)
Objective: To assess the association of Depression with Chronic Low back pain. Methodology: In this cross-sectional investigation, 169 participants with a mean age of 54.1 years were studied at the PN Shifa medical outpatient department in Karachi, Pakistan. The research was conducted over a three-month period, from June to August 2020, using a non-probability convenience sampling approach. The severity of low back pain (LBP) was measured using the Numeric Rating Scale (NRS) and the Wong Baker Faces Pain Rating Scale. To evaluate levels of depression, the Patient Health Questionnaire (PHQ-9) scale was employed. The Chi-square test and one-way ANOVA test were used to establish statistical significance. Results: Patients with moderate to severe chronic low back pain (CLBP) demonstrated higher pain levels on both the Wong Baker Faces Pain Rating Scale and NRS, with a p-value of 0.000. Based on the PHQ-9 scores, severe depression correlated with more intense pain, with a p-value of 0.000, and greater pain severity in the current and previous week (as assessed by the NRS and Wong Baker Faces Pain Rating Scale). A higher percentage of males (34%) experienced mild CLBP compared to females (22%). However, 26% of females were found to suffer from severe CLBP, as opposed to 12% of males, with a p-value of 0.014. Conclusion: Patients with chronic low back pain often experience depression and report high levels of pain.